Implementasi Kode Etik Komunikasi Publik dalam Kebijakan Pemerintah: Kajian Normatif terhadap Praktik Komunikasi Resmi Instansi - Ardiyanto Wardhana (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
The implementation of public communication ethics codes in governmental policies encounters complex challenges in achieving optimal transparency, accountability, and responsiveness standards. This qualitative research employs library research methodology to analyze the effectiveness of public communication ethics code implementation mechanisms through normative examination of official government communication practices. Systematic content analysis of regulations, policies, and communication practice documentation reveals significant disparities between normative idealities and operational realities in field implementation. Findings indicate structural, cultural, and technological factors serve as primary determinants of implementation success. The digital era and post-truth phenomena present additional complexities in managing ethical public communication. Technological adaptation inadequacies, institutional coordination fragmentation, and organizational commitment variations influence the consistency of communication ethics standard application. A comprehensive evaluation model integrating input-process-output-outcome dimensions is essential for measuring implementation effectiveness. Recommendations encompass institutional capacity strengthening, adaptive regulatory framework reformulation, and development of communicative accountability systems responsive to contemporary dynamics. This research contributes to developing theoretical frameworks for public communication ethics code implementation within Indonesian governmental governance contexts.